High-performance metal mesh/graphene hybrid films using prime-location and metal-doped graphene - Min, Jung-Hong (Sci Rep, 2017)
We introduce high-performance metal mesh/graphene hybrid transparent conductive layers (TCLs) using prime-location and metal-doped graphene in near-ultraviolet light-emitting diodes (NUV LEDs). Despite the transparency and sheet resistance values being similar for hybrid TCLs, there were huge differences in the NUV LEDs’ electrical and optical properties depending on the location of the graphene layer. We achieved better physical stability and current spreading when the graphene layer was located beneath the metal mesh, in direct contact with the p-GaN layer. We further improved the contact properties by adding a very thin Au mesh between the thick Ag mesh and the graphene layer to produce a dual-layered metal mesh. The Au mesh effectively doped the graphene layer to create a p-type electrode. Using Raman spectra, work function variations, and the transfer length method (TLM), we verified the effect of doping the graphene layer after depositing a very thin metal layer on the graphene layers. From our results, we suggest that the nature of the contact is an important criterion for improving the electrical and optical performance of hybrid TCLs, and the method of doping graphene layers provides new opportunities for solving contact issues in other semiconductor devices.